Penerapan Project-Based Learning pada Mata Pelajaran Instalasi Motor Listrik - Roza Anggraini; Taali Taali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study aims to determine the increase in student learning outcomes and the proportion of mastery learning outcomes after the implementation of the Project-Based Learning model in the subject of electric motor installation at SMK Negeri 1 Bonjol. This type of research is initial experimental research (Pre-Experiment) with the One Group Pretest Posttest design. The research subjects were students of class XI TITL SMK Negeri 1 Bonjol for the academic year 2022/2023, totaling 33 students. In this study, the data collection method used pretest and posttest questions which were validated by expert assessors, namely subject expert lecturers and subject teachers. before the first treatment is given a pretest (initial test) and at the end of learning is given a posttest (final test). Before being given treatment, they are first given pretest questions (initial test) and at the end of learning are given posttest questions (final test). The results showed that the application of the Project-Based Learning learning model in the class XI TITL electric motor installation subject at SMK Negeri 1 Bonjol can improve student learning outcomes. These results can be seen from the realm of knowledge, namely the results of the pretest and posttest which were analyzed using the N-Gain Score formula into the moderate category and using completeness learning outcomes increase from very low to high categories. Thus the project-based learning model improves student learning outcomes in the electric motor installation subject.